2020
DOI: 10.1002/dta.2771
|View full text |Cite
|
Sign up to set email alerts
|

Hitting the Jackpot – development of gas chromatography–mass spectrometry (GC–MS) and other rapid screening methods for the analysis of 18 fentanyl‐derived synthetic opioids

Abstract: In recent years, the occurrence of synthetic opioid fentanyl and its derivatives has grown significantly in forensic casework. This study presents the synthesis and analysis of 18 fentalogs, selected based on information received from local law enforcement. This study provides colorimetric tests, thin‐layer chromatography (TLC) which can potentially be utilized for presumptive screening of the target compounds, as bulk powders or as trace‐level adulterants. The fully validated confirmatory GC–MS method (employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…This concentration was based on previously reported studies of seized samples within Greater Manchester. [41] Due to the small sample size (n = 7) in these previous studies, the results may not truly reflect the typical levels of fentanyl contained in heroin samples nationally. However, this concentration was chosen to demonstrate that the proposed low-field qNMR method is suitable for the routine screening of suspect samples which may contain fentanyl derivatives at trace levels.…”
Section: F Nmr Calibration Standardsmentioning
confidence: 84%
See 2 more Smart Citations
“…This concentration was based on previously reported studies of seized samples within Greater Manchester. [41] Due to the small sample size (n = 7) in these previous studies, the results may not truly reflect the typical levels of fentanyl contained in heroin samples nationally. However, this concentration was chosen to demonstrate that the proposed low-field qNMR method is suitable for the routine screening of suspect samples which may contain fentanyl derivatives at trace levels.…”
Section: F Nmr Calibration Standardsmentioning
confidence: 84%
“…The solvent system was selected to directly relate the chromatographic data of these novel fluorinated fentanyl derivatives with previously reported fentalogues. [41] The developed plates were observed under UV light (254 nm) and developed with modified Dragendorff-Ludy-Tenger reagent. [42] Six replicate tests were conducted for each compound to calculate the average retention factor (Rf) and relative retention factor (RRf, with respect to fentanyl, 18).…”
Section: Thin Layer Chromatography (Tlc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Since GC-MS is an extensively used technique for fentanyl analysis [30], developing tools and methods using this platform could allow for adoption by a large number of laboratories. Much of the recent work that has been method-based has focused on small subsets of compounds [31] or has been toxicology focused [32,33]. In terms of novel data analysis and interpretation, Gilbert et al demonstrated how principal component analysis can be used for the classification of fentanyl analogues based on their gas chromatography mass spectrometry (GC-MS) spectra [34].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, analytical methods need to be regularly updated to keep up with the constant emergence of new uncontrolled analogs. Currently, some methods have been reported for the determination of fentanyl and its derivatives, such as thin-layer chromatography, high-performance liquid chromatography (HPLC) with ultraviolet and amperometric detection, gas chromatography–mass spectrometry (GC–MS), , HPLC or ultrahigh-performance liquid chromatography (UHPLC) coupled with triple quadrupole or linear ion trap mass spectrometers, etc. Featuring high specificity and selectivity, GC–MS and (U)­HPLC–MS are gold standard methods for drug analysis.…”
mentioning
confidence: 99%